Activity Treatment of Some Long-Lived Radioactive Nuclides Using Thermal Neutron Incineration - Alkazzaz , Hassanain H.; Al-Mashhadani, Asia H.; Lateef , Kamal H. (Iraqi Journal of Science, 2023)
In the present work, the possibility of treating many types of radioactive sources was examined practically. Six types of sealed radioactive sources were selected: 137Cs, 133Ba, 90Sr, 152Eu, 226Ra, and 241Am. The sources were exposed to a neutron flux emitted from 241Am/Be source for 33 days. The results showed a measurable reduction of activity for 226Ra, 241Am, and 152Eu, while the other radionuclides, 137Cs, 133Ba, and 90Sr, showed less response to neutron incineration.